MASTERING THE CLASSROOM: STRATEGIES FOR EFFECTIVE TEACHING, STUDENT ENGAGEMENT, AND TECHNOLOGY INTEGRATION - Durdona Khamidova; Ruxshona Munibullayeva (Western European Studies, 2025)
This paper discusses strategies for improving classroom management, student engagement, and instructional effectiveness. It discusses various pedagogical approaches like active learning, differentiated instruction, and formative assessments. The study suggests that a combination of structured classroom management, interactive teaching methods, and continuous feedback significantly enhances student performance.
Keywords: Classroom management; active learning; student engagement